The Austrian Pay Transparency Law and the Gender Wage Gap - René Böheim; Sarah Gust (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In Austria, a gender pay transparency law was introduced in 2011, requiring companies with more than 1,000 employees to publish a pay report every other year. Firms with 500, 250, and 150 employees were subject to this requirement at later years. We estimate the impact of the law on men's wages, women's wages, and the gender pay gap using administrative data. The results from a regression discontinuity design suggest that the wage transparency law did not change wages or the gender wage gap. In larger firms, the wage of newly hired women increased more due to the reform than of newly hired men, suggesting that the gender wage gap decreased among newly hired workers. Our estimates of the effect of the law on employment growth or turnover are small, and statistically insignificant. For larger firms, we estimate that the transparency law led to a lower share of women in treated firms. These results are robust to several additional specifications.
Keywords: J31; 330; wage transparency; gender wage gap